Dóniz-Páez, J. & Pérez, N.M. (Editors), 2023. El Hierro Island Global Geopark: Diversity of Volcanic Heritage for Geotourism. Springer, Cham. vii+123 pp. ISBN 978-3-031-07288-8. DOI: 10.1007/978-3-031-07289-5. - Dmitry Ruban (Geoconservation Research)
The new book edited by Dóniz-Páez & Pérez presents the experience and the findings of the multi-aspect research undertaken in the El Hierro UNESCO Global Geopark (UGGp) established in the Canary Islands of Spain for about a decade. Taking into account the general importance and the diversity of the topics considered in this book, the latter deserves the attention of the international research community. It should be highlighted that this geopark represents chiefly volcanic geoheritage, and, thus, the volume bears a lot of information about volcanism.